In-depth characterization of minor 2-(2-phenylethyl)chromone oligomers from Chinese agarwood by integrating offline two-dimensional liquid chromatography and hybrid ion trap time-of-flight mass spectrometry - Huixia Huo; Hang Zhang; Huiting Liu; Jiale Ma; Qian Zhang; Yunfang Zhao; Jiao Zheng; Pengfei Tu; Yuelin Song; Jun Li (Chinese Medicine)
Abstract Those minor, even trace natural products sometimes exhibit exciting activities and possess unique structures; however, it is challenging to pursue and identify such components using routine LC−MS/MS platforms attributing to their low distribution levels in herbs, the overlapping effects from the abundant ingredients and the high-level structural diversity. Here, an off-line two-dimensional liquid chromatography hook up hybrid ion trap time-of-flight mass spectrometry program was exploited to facilitate the exposure of those minor components in chromatographic domain and to acquire high-resolution multi-stage mass spectra, and the less abundant 2-(2-phenylethyl)chromone (PEC) oligomers from Chinese agarwood that is one of the most precious herbal medicines were concerned to illustrate and assess the applicability towards capturing and structurally annotating those minor components. The mass fragmentation pathways of PEC dimers, in particular the linkage fission between monomers, were proposed by assaying eighteen authentic compounds that covered different conjugation manners, and subsequently applied for the tentative structural identification of observed components. Thereafter, targeted purification was conducted to generate eight new, trace PEC dimers to justify the annotated structures. As a result, heterocyclic ring fission was the diagnostic fragmentation pathways for PEC dimers. In total, 199 PECs were discovered and characterized, consisting of 74 dimers and five trimers. Noteworthily, after structural identification with NMR assays, the confirmative structures of those eight new PEC dimers agreed well with the identities suggested by mass fragmentation rules. Above all, PEC derivatives, notably trace oligomers, in Chinese agarwood were profiled in depth, resulting in a number of interesting structures.